LncRNA MEG3 exacerbates diabetic cardiomyopathy via activating pyroptosis signaling pathway - Zhuo, Shengnan; Liu, Yifeng; Wang, Siyuan; Chen, Zhuoling; Shi, Xuran; Zhang, Yangjunna; Xu, Dengfeng; Hu, Jingjin; Wang, Yin; Qu, Xuefeng (Frontiers in Pharmacology, 2025)
Background: Diabetic cardiomyopathy (DCM) is a prevalent complication observed in diabetic patients. The long non-coding RNA maternally expressed gene 3 (lncMEG3) has been found to be intricately associated with myocardial infarction and heart failure. However, the role of lncMEG3 in DCM remains unclear. The present study was designed to investigate the role of lncMEG3 in DCM and elucidate the underlying molecular mechanisms.Methods: The diabetic mouse model was established through intraperitoneal injection streptozotocin (STZ). The heart-targeted adeno-associated virus carrying lncMEG3 interfering RNA (AAV9-shMEG3) was administered via tail-vein injection to induce silencing of lncMEG3 in diabetic mice. Echocardiography was performed to evaluate cardiac function, while hematoxylin and eosin (H&E) staining and Masson trichrome staining were employed for the detection of cardiac remodeling. The underlying mechanisms were investigated using Western blot and real-time PCR (qPCR).Results: The expression of lncMEG3 was increased in hearts with DCM and in AC16 cardiomyocytes treated with high glucose. The knockout of lncMEG3 reduced inflammation, cardiac fibrosis and myocardial hypertrophy, and improved cardiac dysfunction in diabetic mice. In diabetic mice, the activation of the nucleotide-binding oligomerization domain-like receptor pyrin domain containing 3 (NLRP3)-inflammasome was observed, whereas silencing of lncMEG3 resulted in a reduction in NLRP3 inflammasome activation. Mechanistically, we discovered that lncMEG3 specifically functions as a competitive inhibitor of miR-223. Moreover, the use of miR-223 antisense oligonucleotide (AMO) counteracted the suppressive effects of lncMEG3 knockdown on NLRP3 inflammasome activation induced by high glucose in vitro.Conclusion:LncMEG3 exacerbates DCM by enhancing NLRP3 inflammasome activation through attenuating miR-223-mediated degradation of NLRP3 in the hearts of individuals with diabetes.